Workplace Bullying and Victimization: A Mixed Method Approach - Stylianou, Ifigenia; Stavrinides, Panayiotis; Panayiotou, Alexia; Fanti, Kostas (International Journal of Criminology and Sociology, 2023)
Purpose: The main scope of the survey was to examine how school bullying and victimization experiences affect workplace bullying and victimization, as also the role of the personality traits and workplace environment to this relation. It also aimed to investigate the consequences on mental health of employees who are targets of workplace victimization, as well as the reaction mechanisms of employees against bullying. Method: 302 employees from four private companies in Cyprus completed the Organizational Culture Assessment Instrument, Five Factor Personality Inventory Questionnaire, Retrospective Bullying Questionnaire, Post-traumatic Embitterment Disorder Self-Rating, Negative Acts Questionnaire – Revised, and a list of coping skills, in one-time phase. Results: Based on the results, school victimization experiences and neuroticism, influenced the occurrence of workplace victimization, as also workplace climate affected the above relationship. Workplace climate, workplace victimization and neuroticism, found to be related with the development of Post-Traumatic Embitterment Disorder. In addition, neuroticism and workplace victimization mediated by employees’ coping skills.